Like-simile and metaphor in cooperation: from expressing similarities to expressing contrasts - Reda Ghsoon (Language and Semiotic Studies)
Cognitive-oriented work on simile has developed out of attempts to pinpoint features distinguishing simile and metaphor. This development has had such consequences as 1) focusing on simile as an analogy-based process and 2) giving very little attention to the way simile and metaphor work together, treating them as independent rather than cooperating phenomena. Addressing these shortcomings, this study examines the ability of non-ironic like-simile to imply contrasts between the asserted source-target similarity and a thought or belief evoked by this similarity, giving rise to context-bound attitudinal and illocutionary implications. In cases of like-simile scaffolded by metaphors, the contrast-based process arises from the cooperation of the two phenomena in the sense that the scenario created by the like-simile rests on manipulating the conceptual metaphor(s) supporting the comparison. The analysis of these cases is placed in the Extended Conceptual Metaphor Theory (ECMT) – a contextual, multilevel theory of figurative language conceptualisation. The contrast-based process, drawn from the model of irony developed within the Lexical Constructional Model (LCM), is added to this theory as a mental-space level activity. Raykowski’s sensory schema (a generalized notion of accumulation intuitions) is also added above the image-schema level metaphors, presenting the manipulation of the scaffolding metaphors as based on the expression of this schema.